Developing Metrics for NASA Earth Science Interdisciplinary Data Products and Services. (11th February 2022) - Liu, Zhong; Shie, Chung-Lin; Ritrivi, Anthony J.; Lei, Guang-Dih; Alcott, Gary T.; Greene, Mary; Acker, James; Wei, Jennifer C.; Meyer, David J.; Li, Angela; Al-Jazrawi, Atheer F.
Metrics are measures that are able to produce quantifiable information. There are many applications of metrics in Earth science data and services; for example, metrics are frequently used to track service performance and progress. In short, developing, collecting and analyzing metrics are essential activities to better support Earth science research, applications, and education. As one of the largest repositories of Earth science data in the world, NASA's Earth Science Data and Information System (ESDIS) Project supports twelve Distributed Active Archive Centers (DAACs). Standard metrics have been developed by the ESDIS Metrics System (EMS). These metrics are collected and analyzed routinely at each DAAC. As it is expected that the total data volume will continue to grow rapidly, and the timely developed technologies (e.g., cloud computing, AI/ML) will continue to improve data discovery and accessibility, opportunities for developing new data services for the Earth science community will also arise, especially in interdisciplinary research and applications. However, developing such metrics has become a challenge because multiple datasets are often needed. Current metrics are designed for a single predefined dataset or service, a disadvantage for collecting metrics for interdisciplinary data services. In this paper, we assess current metrics using one of the NASA DAACs, the NASA Goddard Earth Sciences Data and Information Services Center (GES DISC), as an example, to discuss challenges and opportunities, along with recommendations for developing metrics addressing interdisciplinary satellite data products and services. Highlights: Overview of NASA GES DISC Earth science datasets and services Overview of existing metrics collection methods and analysis tools with examples Discuss challenges and opportunities in collecting metrics for Earth science interdisciplinary data and services